Smart-Valleys: A locally led innovation enhancing rice yields, farmer incomes, climate resilience in West African Inland Valleys - Dossou-Yovo, E.R.; Djagba, J.; Kone, P.; Akodekou, A.D. (2025)
Rice is a staple food for over million of people in West Africa, yet regional production meets only ~60% of demand, leaving the region highly dependent on imports. Inland valleys, seasonally wet lowlands hold significant potential for sustainable intensification of rice systems but remain underutilized due to poor water control, suboptimal agronomic practices, and socio-institutional barriers. The Smart-Valleys approach, developed by AfricaRice, is a participatory, low-cost, locally led adaptation strategy that integrates simple water-control infrastructure, farmer-driven land-use planning, and context-specific agronomic management. This study evaluates the agronomic, economic, and ecological performance of Smart-Valleys across 243 inland valleys in seven West African countries spanning humid, sub-humid, and semi-arid agro-ecological zones. Results show that Smart-Valleys increased rice yields by 2.1 t/ha on average, enhanced net household income by USD 946/ha, and improved benefit-cost ratios relative to adjacent non-developed inland valleys. Key drivers of yield variation included soil fertility, rainfall, temperature, and management practices such as fertilizer application, herbicide, and disease control. Beyond productivity gains, Smart-Valleys strengthens climate resilience, empowers local communities, and supports ecosystem service provision, including water regulation and nutrient cycling. The approach aligns with global Locally Led Adaptation principles by placing communities at the center of adaptation decision-making, promoting inclusive participation, adaptive management, and scalable, cost-effective solutions. Evidence from this study highlights Smart-Valleys as a viable model for integrating climate resilient agricultural development with sustainable landscape management and locally led adaptation in West Africa.